CMT307: Industrial Process / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2017)
Industrial health and safety and environmental pollution are the main issues in manufacturing process industries. Knowledge on processing of materials such as cement, palm oil, petroleum and paint are discussed. Students are exposed to the chemically related manufacturing industries in Malaysia. Students will have the opportunity to go for plant visits or field trips or attend a career talk.